CHP (combined heat and power) retrofit for a large MED-TVC (multiple effect distillation along with thermal vapour compression) desalination plant: high efficiency assessment for different design options under the current legislative EU framework. (15th November 2016) - Tamburini, A.; Cipollina, A.; Micale, G.; Piacentino, A.
Abstract: Integrated power plants in "dual purpose" configuration may represent a viable option for energy cost abatement of desalted water produced by MED-TVC (Multiple Effect Distillation along with Thermal Vapour Compression). In this paper an existing large MED-TVC plant with a 36, 000 m 3 /day capacity is studied: a plant retrofit is designed, based on a steam power plant with condensation and steam extraction used to drive the steam ejector. As the plant operates in CHP (Combined Heat and Power) mode, the possibility to assess the integrated "CHP + MED-TVC" as high efficiency cogeneration according to Directive 2004/8/EC is discussed. Based on a model developed in Engineering Equation Solver, a sensitivity analysis is performed: the influence of several design and operation parameters on the fraction of energy outputs assessed as "from efficient cogeneration" is investigated. This fraction was found to increase almost linearly with the number of MED units supplied with steam. Also, when all the MED units are supplied and the steam extraction pressure is decreased from 4.89 MPa down to 0.29 MPa, the CHP fraction increased from ∼54% to ∼77%. The assessment of the plant as "high efficiency CHP" was found highly dependent on the specific fuel adopted. Highlights: A CHP retrofit for an existing MED-TVC desalination plant is designed. A physical model is developed to simulate several design and operating conditions. The dual-purpose plant is assessed with reference to the provisions of CHP-Directive. The steam extraction pressure and flow rate heavily influence the PES index. The plant can be assessed or not as "high efficiency CHP", depending also on the fuel used.